PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XII MIPA 1DI SMAN 1 KOTA JAMBI - Marpaung, Iknatius Suriani; Sembiring, Benar (SJEE (Scientific Journals of Economic Education), 2022)
This study aims to find out (1) How is student learning independence in economics class XII MIPA at SMAN 1 Jambi City. (2) How are student learning outcomes in economics class XII MIPA at SMAN 1 Jambi City. (3) The effect of independent learning on student learning outcomes in economics class XII MIPA at SMAN 1 Jambi City. This research was conducted using descriptive quantitative research methods, with data collection techniques through observation, interviews, and questionnaires. Where the population in this study were 142 students with a sample of 104 students. The data processing techniques in this study are Research Instrument Validation Test, Research Instrument Reliability Test, Quantitative Descriptive Analysis, Normality Test, Homogeneity Test, Heteroscedasticity Test and Simple Regression Test. The results showed that (1) learning independence got a TCR score of 79.43% in the Good Enough category. (2) The calculation results show that the students' learning outcomes in economics subjects who scored above the minimum completeness criteria (KKM) 6.7 were 57 students, and 35 students who obtained scores below the minimum completeness criteria (KKM) 6.7 student. (3) From the results of simple regression analysis calculations, there is an effect of learning independence (X) on learning outcomes (Y) of 23.1% with proven t-test results of 2.393 which is greater than t-table which is 1.983. Which states that HI is accepted and Ho is rejected. Keywords: Independent Learning, Learning Outcomes